1996
DOI: 10.1016/0893-133x(95)00178-g
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Correlation of Inhibitory Gating of Hippocampal Auditory Evoked Response and α-Bungarotoxin-Binding Nicotinic Cholinergic Receptors in Inbred Mouse Strains

Abstract: One function of the hippocampus is to ascertain the novelty of incoming sensations and encode significant new information into memory. The regulation of response to repeated stimuli may prevent overloading of this function by redundant sensory input. Recent pharmacological studies implicate the role of alpha-bungarotoxin-sensitive nicotinic cholinergic receptors in the inhibition of hippocampal response to repeated auditory stimuli. The number of hippocampal alpha-bungarotoxin-sensitive receptors has a major g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
190
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(204 citation statements)
references
References 47 publications
12
190
2
Order By: Relevance
“…The amplitude from the peak of the P20 to the trough of the N40 was then calculated to facilitate comparison with previous literature, as it is reported to be a more stable measure than either component alone (Cook et al, 1968;Stevens et al, 1996). A repeated-measures ANOVA was used to evaluate the effects of drug and ISI for each component analyzed.…”
Section: Effects Of Haloperidol and Olanzapine On The Mouse Auditory mentioning
confidence: 99%
See 1 more Smart Citation
“…The amplitude from the peak of the P20 to the trough of the N40 was then calculated to facilitate comparison with previous literature, as it is reported to be a more stable measure than either component alone (Cook et al, 1968;Stevens et al, 1996). A repeated-measures ANOVA was used to evaluate the effects of drug and ISI for each component analyzed.…”
Section: Effects Of Haloperidol and Olanzapine On The Mouse Auditory mentioning
confidence: 99%
“…Additionally, the P20/N40 difference waveform was calculated to facilitate a comparison with previous literature (Cook et al, 1968;Stevens et al, 1996). This animal model is intended to elucidate the neurobiology of sensory processing as well as helping to clarify differences among the effects of different antipsychotic medications on sensory processing phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…1,[33][34][35] Compared with controls, patients with schizophrenia and psychotic bipolar disorder have a relatively larger P50 response to the second stimulus, from only 20-50% suppression. 31,[36][37][38][39][40][41][42][43][44][45][46][47] Clinically unaffected first-degree relatives of patients with schizophrenia and psychotic bipolar disorder also have poor P50 suppression, suggesting that this might act as a marker of genetic risk for these disorders, [46][47][48][49][50][51][52][53] as it is heritable. [54][55][56][57] We have examined the effects of CHRFAM7A CNV/2 bp deletion variants on the major psychoses and the P50 sensory gating deficit.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that major behavioral alterations have not been seen in ␣7 nAChR 129SvEv knockout mice (Orr-Urtreger et al, 1997;Paylor et al, 1998;Franceschini et al, 2000Franceschini et al, , 2002. Initial studies from our laboratory, however, have indicated that the basal level of ␣-BGT binding to the hippocampi of wild-type 129SvEv mice is 31 Ϯ 10 fmol/mg protein (Pereira, Fawcett, Randall, and Albuquerque, unpublished results) and poor gating of auditory responses has been observed in inbred mice strains with ␣-BGT-binding levels Ͻ30 fmol/mg protein in the hippocampus (Stevens et al, 1996). Therefore, it is possible that, as a consequence of low levels of ␣7 nAChR expression, there are modifications in higher brain functions of the wild-type 129SvEv mice that mask behavioral changes resulting from the null mutation in the gene coding for the ␣7 nAChR subunit.…”
Section: Introductionmentioning
confidence: 99%